2001
DOI: 10.1002/bit.1064
|View full text |Cite
|
Sign up to set email alerts
|

Design of transgenes for efficient expression of active chimeric proteins on mammalian cells

Abstract: Heterologous proteins expressed on the surface of cells may be useful for eliciting therapeutic responses and engineering new extracellular properties. We examined factors that control the membrane targeting of ␣-fetoprotein (AFP) and a single-chain antibody (scFv). Chimeric proteins were targeted to the plasma membrane by employing the transmembrane domain (TM) and cytosolic tail of murine CD8O (B7-1), the TM of the human platelet-derived growth factor receptor (PDGFR), the glycosylphosphatidylinositol anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…We previously showed that the murine B7-1 TM and intact cytoplasmic tail allowed high expression of AFP 19 and scFv 15 due to rapid transport and stable retention of the proteins on the cell surface. 18 In the present investigation we tested the hypothesis that introduction of a spacer domain containing oligosaccharides at the juxtamembrane position of chimeric receptors could further increase surface expression by reducing shedding. The rationale for this hypothesis was based on the observation that many endogenous receptors contain serine-and threonine-rich domains near the cell membrane that are potential sites of O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that the murine B7-1 TM and intact cytoplasmic tail allowed high expression of AFP 19 and scFv 15 due to rapid transport and stable retention of the proteins on the cell surface. 18 In the present investigation we tested the hypothesis that introduction of a spacer domain containing oligosaccharides at the juxtamembrane position of chimeric receptors could further increase surface expression by reducing shedding. The rationale for this hypothesis was based on the observation that many endogenous receptors contain serine-and threonine-rich domains near the cell membrane that are potential sites of O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that 2C11-B7 already represented an improved surface receptor since it allowed about 5-10 times greater amounts of scFv to accumulate on cells as compared to the prototype scFv receptor (2C11-PDGFR). 15,18 The presence of oligosaccharide chains in the linker domain was mandatory for increased surface expression because removal of glycosylation acceptor sites (2C11-BGP3-B7) reduced surface expression to levels even below those observed without introduction of a linker (Fig 2b). Both O-linked (2C11-CD44-B7) and N-linked (2C11-BGP-B7, 2C11-g1-B7 and 2C11-e-B7) glycosylation effectively reduced shedding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously performed a series of studies to determine the optimal conditions for the expression of proteins 32 and scFv 26,28,33 on mammalian cells. The transmembrane domain and cytoplasmic tail derived from the B7-1 antigen was found to facilitate rapid intracellular transport of chimeric proteins to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 In the present study, the anti-phOx scFv was fused to the transmembrane (TM) domain and cytoplasmic tail of murine CD80, which we have previously shown to direct efficiently the expression of heterologous proteins to the cell surface. 14 The utility of surface receptor targeting was investigated by covalently attaching phOx moieties to b-glucuronidase (bG) to create a ligand for specific recognition and binding to cells that display phOx scFv receptors. The present study investigated whether the accumulation of phOx-modified bG at receptor-positive cells could allow preferential activation of a glucuronide prodrug (p-hydroxy aniline mustard b-D-glucuronide, HAMG) for selective cell killing (Fig 1).…”
mentioning
confidence: 99%